A test of the rational expectations hypothesis using data from a natural experiment - Anna Conte; Peter G. Moffatt; Fabrizio Botti; Daniela T. Di Cagno; Carlo D'Ippoliti (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Data on contestants' choices in Italian Game Show Affari Tuoi are analysed in a way that separates the effect of risk attitude (preferences) from that of beliefs concerning the amount of money that will be offered to contestants in future rounds. The most important issue addressed in the paper is what belief function is actually being used by contestants. The parameters of this function are estimated freely along with the parameters of a choice model. Separate identification of the belief function and preferences is possible by virtue of the fact that at a certain stage of the game, beliefs are not relevant, and risk attitude is the sole determinant of choice. The rational expectations hypothesis is tested by comparing the estimated belief function with the true offer function which is estimated using data on offers actually made to contestants. We find that there is a significant difference between these two functions, and hence we reject the rational expectations hypothesis. However, when a simpler rule-of-thumb structure is as- sumed for the belief function, we find a correspondence to the function obtained from data on actual offers. Our overall conclusion is that contestants are rational to the extent that they make use of all available relevant information, but are not fully rational because they are not processing the information in an optimal way. The importance of belief-formation is confirmed by the estimation of a mixture model which establishes that the vast majority of contestants are forward-looking as opposed to myopic.
Keywords: C15; C23; C25; D81; 330; Beliefs; Discrete choice models; Method of simulated likelihood; Natural Experiments; rational expectations; risky choice; Rationale Erwartung; Diskrete Entscheidung; Entscheidung bei Risiko; Glücksspiel; Test; Italien